Time-sensitive supply chain disruption recovery and resource sharing incentive strategy - Hongguang Bo; Yinglian Chen; Huanzhi Li; Peng Han; Lian Qi (Journal of Management Science and Engineering, 2021)
Market demand is becoming increasingly time-sensitive in competitive environments. Hence, supply disruptions will have a more serious impact on the profits of supply chains. This study applies a Stackelberg competition between a single supplier and a single manufacturer in a time-sensitive supply chain in a cloud manufacturing environment. We aim to address the supplier’s production capacity recovery issues and the manufacturer’s incentive decision issues after supply disruption. We find that the supplier is in a weak position when the information is symmetrical. The manufacturer can encourage the supplier to shorten the recovery time by raising the unit wholesale price. When the supplier’s unit production cost remains unchanged but the unit wholesale price increases, the profit of the supplier first increases and then decreases. In addition, under the centralized decision-making setting, the optimal recovery time of the supplier is shorter and the optimal unit market price of the product is lower than that under decentralized decision-making. We further find that resource sharing can shorten the optimal recovery time, but it does not necessarily play an incentivizing role.